ISLAMIC LAW PARADIGM (CLASSIC AND ALTERNATIVE) - Nunung Susfita (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
Paradigm is a collection of assumptions, concepts, and proportions that are logically put together and function to direct thought and study. Celestial religion before Islam has a limited capacity of time and place. The temporary nature is limited by the presence of the Prophet afterwards, such as the teachings of Musa a.s. The deadline is when the teachings of Isa a.s arrived. In contrast, the religion of Islam brought by the Prophet Muhammad is the last and final religion. The Qur'an is essentially a document of diversity and ethics that aims to be practical, to create a society of good morality and justice. The doctrine of freedom of human will as proclaimed by the Mu'tazillah is part of the theological concept of God's justice and defeats the original aspect of freedom and human responsibility. Among Orthodox, this human freedom means God's indifference. They accused the Mu'tazilah sect as extreme humanism, they asserted that God is outside the human concept of justice. What human beings see as God's justice does not mean that to Him, but what He does for humans does seem fair and rational to humans.